Pengembangan Instrumen Penilaian Pelajaran Bahasa Indonesia MI - Ahmad Noviansah; Hascita Istiqomah (Al - Azkiya : Jurnal Ilmiah Pendidikan MI/SD, 2020)
All teaching and learning processes always have goals to be achieved, those goals can be known to be successful or not by making an assessment. Assessment is a very important activity in the teaching and learning process. The purpose of the assessment itself is to know the extent of the students' ability to understand the lessons in each learning activity. Teachers are also required to be able to develop assessment instruments in all subjects, especially Indonesian language subjects. As a teacher, it would be nice to know how to make assessment instruments well and efficiently. Because a good and efficient instrument will produce good results and will make it easier for teachers to assess student learning outcomes. We can see in some schools there are still many teachers who do not understand how to develop assessment instruments correctly and easily understood. So the way of assessment in evaluation activities carried out by teachers is still lacking. This paper will discuss how teachers develop correct and easy-to-understand assessment instruments that will be used as a reference in assessing students' learning processes. From this assessment, teachers can find out the success rate of students in the learning process in Bahasa Indonesia subjects. And teachers can find out the extent of their success in the teaching process.